Casos y cosas: semanario popular (Vol. 2, No. 73) - Imprenta La Region (My University, 1921)
SPANISH: Incluye: Efectos de la dictadura, Desterrando Inmoralidades, Otro fracaso del Prefecto, Veinte y seis contos se esfuman en Lisboa....?, El ex-suprefecto y sus fechorias, A una señora elegante.

ENGLISH: Includes: Effects of dictatorship, Banishing Immoralities, Another failure of the Prefect, Twenty-six contos vanish in Lisboa....?, The ex-supreme and his misdeeds, To an elegant woman.
Cases and things: popular weekly magazine (Vol. 2, No. 73)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas